N-(3,4-Dimethylphenyl)acetamide - Gowda, B. Thimme (International Union of Crystallography, 2007)
The conformation of the N—H bond in the title compound (34DMPA), C(10)H(13)NO, is syn to the 3-methyl substituent in the aromatic ring, in contrast to the anti conformation observed with respect to the 3-chloro substituent in N-(3,4-dichlorophenyl)acetamide (34DCPA). The asymmetric unit of the structure contains three molecules. The bond parameters in 34DMPA are similar to those in 34DCPA, N-(2,6-dimethylphenyl)acetamide, N-(3,5-dimethylphenyl)acetamide and other acetanilides. The molecules in 34DMPA are linked into infinite chains through N—H⋯O hydrogen bonding.